2010
DOI: 10.1007/s00464-010-0893-5
|View full text |Cite
|
Sign up to set email alerts
|

Effort, safety, and findings of routine preoperative endoscopic evaluation of morbidly obese patients undergoing bariatric surgery

Abstract: Upper gastrointestinal endoscopy can be performed safely. However, careful monitoring and anesthesiological support are required for patients with concomitant diseases and those receiving sedation. Because 80% of the patients with pathological findings were asymptomatic, every morbidly obese patient should undergo endoscopy before bariatric surgery because there may be findings that might change the surgical strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 31 publications
(37 reference statements)
1
42
2
4
Order By: Relevance
“…However, opponents argue that the yield of routine preoperative OGD is low and is not cost-effective [9]. It also does not justify exposing obese patients to the risks of OGD, which can be tenfold greater than compared to the average population [20]. Morbidly obese patients are more likely to have concomitant diseases; diabetic obese patients may experience glycaemic complications due to the fasting for OGD.…”
Section: Discussionmentioning
confidence: 98%
“…However, opponents argue that the yield of routine preoperative OGD is low and is not cost-effective [9]. It also does not justify exposing obese patients to the risks of OGD, which can be tenfold greater than compared to the average population [20]. Morbidly obese patients are more likely to have concomitant diseases; diabetic obese patients may experience glycaemic complications due to the fasting for OGD.…”
Section: Discussionmentioning
confidence: 98%
“…Im resezierten Magenabschnitt befinden sich zahlreiche ghrelinproduzierende Zellen. Hierdurch sinkt postoperativ der Plasmaghrelinspiegel; dies geht mit einem verminderten Hungergefühl einher [27]. Falls der Gewichtsverlust nicht ausreichend ist, kann später ein "Roux-en-Y gastric-bypass" angeschlossen werden [26].…”
Section: Schlauchmagenoperationunclassified
“…Die Prävalenz von Hiatushernien und gastroösophagealem Reflux ist bei adipösen Patienten (BMI > 30 kg/m 2 ) im Vergleich zu normalgewichtigen Patienten mehr als verdoppelt [6]. In einer weiteren aktuellen Untersuchung wurden bei fast 80% der extrem adipösen Patienten mithilfe einer präoperativen Gastroösopha-goduodenoskopie pathologische Befunde erhoben, obwohl nur 20% der Patienten vorher symptomatische Beschwerden angegeben hatten [27]. Deshalb ist bei extrem adipösen Patienten von einer erhöhten Aspirationsgefahr auszugehen.…”
Section: Nüchternheitsgebot Antacida Und Anxiolytikaunclassified
“…Published guidelines from the European Association for Endoscopic Surgery (EAES) in 2005 and the American Society of Gastroenterology (ASGE) in 2008 recommended that upper gastrointestinal endoscopy should be performed in all symptomatic patients undergoing bariatric surgery, and considered in all candidates [1,2]. However, the rationale for using routine endoscopy in asymptomatic patients before bariatric surgery remains contentious [3][4][5][6][7][8][9][10]. Several authors have now documented the lack of correlation between patient symptoms and endoscopic findings and have suggested that routine preoperative endoscopy might in fact be useful in detecting both lesions and inflammation [11,12].…”
Section: Introductionmentioning
confidence: 99%